(untitled) (Itinera, 2022)
This paper discusses the empirical findings concerning the visual aesthetic experience in a neurological context. Accordingly, the aim of this paper is to shed light on the common ground across neuroscience, psychology, and philosophy to pave new roads for empirical research. Cognitive models posit that the brain employs neural networks mediating bottom-up and top- down processes, and in effect, engenders emotion and reward throughout the visual aesthetic experience. Likewise, empathy and its corresponding recruitment of bodily processes may facilitate the understanding of a visual artwork’s depicted emotion, which may allow the viewer to engage with the visual artwork from a psychological distance and, consequently, to experience pleasure regardless of the visual artwork’s emotional content. In conclusion, empathetic processes may be central to the visual aesthetic experience and should be considered by future empirical research investigating the visual aesthetic experience.